A Knowledge Representation Framework Based on Epistemic Logic - Teodor Przymusiński (Zeszyty Naukowe Warszawskiej Wyższej Szkoły Informatyki, 2014)
We introduce a uniform non-monotonic framework for knowledge representation based on epistemic logic which is sufficiently general to encompass several nonmonotonic formalisms, including circumscription, autoepistemic logic, various semantics proposed for logic programs and deductive databases (stable semantics, well-founded semantics and stationary semantics) as well as Gelfond’s epistemic specifications. The existence of such a uniform framework allows us not only to provide simpler and perhaps more natural definitions of various formalisms but it also enables us to better understand mutual relationships existing between them.